Design and control of a grid-connected solar-wind hybrid sustainable energy generation systems using DFIG - Kumar, G. B. Arjun; Balamurugan, M.; Kumar, K. N. Sunil; Gatti, Ravi (Institute of Advanced Engineering and Science, 2025)
An optimal control of a grid-connected solar-wind hybrid scheme for the electricity generation system by utilizing both wind and solar renewable energy in a remote region that is inaccessible to the electricity grid. The control and assessment of a hybrid sustainable energy generation system power system that supplies three-phase, four-line loads as well as a battery array are presented in this research work. Wind energy conversion system (WECS) is comprised of a doubly-fed induction generator (DFIG) and two pulse width modulation (PWM) voltage source converters, namely the grid side converter (GSC) and the rotor side converter (RSC), which are linked together via a DC-link and are equipped with a technique for maximum power point tracking (MPPT). The grid voltage-oriented control strategy is employed to provide a consistent DC-bus voltage for the GSC and to regulate the reactive power on the power grid. Even the difference in voltage and frequency can be controlled with this novel strategy. The stator voltage-oriented vector technique is designed in the RSC control strategy, resulting in effective regulation of reactive and active power at the stator as well as an MPPT obtained by controlling the optimal torque. The hybrid sustainable energy generating system (HSEGS) simulation model is designed to have a capacity of 5 kW, and its efficiency is evaluated using the MATLAB/ Simulink platform and demonstrated in a variety of circumstances.